PHYLOGENETIC DIVERSITY OF THERMOPHILIC BACILLI ISOLATED FROM GEOTHERMAL SPRINGS OF NAGORNO KARABAKH (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Totally twenty three thermophilic bacilli strains were isolated from Karvachar (70ºC) and Zuar (42ºC) geothermal springs of Nagorno Karabakh. The comparison of generated 16S rDNA sequences of the isolates with the ones available in GenBank database indicates their relations to nine species distributed in four genera: Aeribacillus (A. pallidus), Anoxybacillus (A. flavithermus, A. suryakundensis, A. rupiensis, Anoxybacillus sp.), Bacillus (B. licheniformis, B. simplex, B. cereus) and Geobacillus (G. toebii). Representatives of genus Anoxybacillus was dominated in the Karvachar geothermal spring composing 67% of all detected isolates. Zuar spring was populated by representatives of A. rupiensis and G. toebii.
Keywords: geothermal springs, thermophilic bacilli, $Bacillus$, $Anoxybacillus$, $Aeribacillus$ and $Geobacillus$, 16S rRNA gene sequencing